Tyrosinase‐Conjugated Prussian Blue‐Modified Nickel Oxide Nanoparticles‐Based Interface for Selective Detection of Dopamine. Issue 21 (28th July 2017) - Roychoudhury, Appan; Prateek, Arneish; Chauhan, Neha; Kumar, D. S.; Basu, Suddhasatwa; Jha, Sandeep K.
Abstract: In this paper, we have reported fabrication of a label free dopamine biosensor with improved sensitivity and selectivity using an interface based on Prussian blue (PB) modified nickel oxide (NiO) nanoparticles (NPs) and tyrosinase enzyme conjugates. A wet chemical sol‐gel method was used to synthesize NiO NPs followed by surface modification with PB and utilized as a matrix to immobilize tyrosinase. The structural and morphological studies of the prepared NPs were conducted using X‐ray diffraction (XRD), high resolution transmission electron microscopy (HR‐TEM), Raman and UV‐Vis spectroscopy and purity of the sample was confirmed through X‐ray photoelectron spectroscopy (XPS), energy dispersive X‐ray spectroscopy (EDX) and Fourier transform infrared spectroscopy (FTIR) studies. Subsequently, the PB modified NiO NPs were deposited onto a flexible screen printed carbon electrode (SPCE) substrate and tyrosinase enzyme molecules were immobilized onto PB‐NiO NPs functionalized SPCE by covalent immobilization for selective and sensitive detection of neurotransmitter dopamine. The enzyme immobilization was confirmed through scanning electron microscopy (SEM) and FTIR studies and the fabricated electrode was used for electrochemical detection of dopamine using cyclic voltammetry and chrono‐amperometric methods. The results of the electrochemical response studies revealed high sensitivity of 60.459 μA/nanomoles in a broad detection range (0.0075‐1.5 nanomoles) with a detection limit of 3.117 picomoles, whereas sample volume was as low as 15 μL. The proposed sensor exhibited fast response time of 24 seconds; good selectivity in presence of interferents ascorbic and uric acid; descent shelf life of 50 days with excellent reusability (>30 times with 78 % residual response). The sensor was also successfully validated with spiked real serum samples. Abstract : Prussian blue (PB) modified nickel oxide (NiO) NPs have been successfully prepared and functionalized with tyrosinase enzyme molecules for selective detection of dopamine by electrochemical techniques. The fabricated biosensor exhibited high sensitivity (60.46 μA/nanomoles) and linearity in a wide detection range (0.0075‐1.5 nanomoles) with one of the best LOD of 3.117 picomoles for dopamine within 24 seconds response time. Moreover, the sensor exhibited a descent storage stability (50 days) with good reusability and low sample requirement (15 μL) which makes it an effective biosensor.